Fotografi Ekspresi : â€œPermainan Bentuk Tubuh Manusiaâ€ - Purwastya Pratmajaya Adi Lukistyawan (Institut Seni Indonesia Surakarta, 2012)
Photography in general as a tool for documentation of an event or incident. Along with the advancement of technology and the development of human creative ideas, then photography captured managed to make a more unique and different. Photography is designed with a particular concept, processed and presented as an artistic expression discharges took it, then it becomes a work of photographic expressionÂ works .(Soeprapto Soedjono, 2007; 27). Photographic expression of the theme of the body shape is a creation of photography as an expression of the author's personal expression in response to the artistic value of body shape. Based creative ideas, the author will explore the form of the human body, which then drafted, processed and presented as an expression of the authors discharges. In the creation of works of art, the game is something that is autonomous.Â The game will be the occasion of pure appearance, a structure,Â work independently. Independence will give size of meaning (BambangÂ Sugiharto, Agus Rachmat W, 2000, 251). In the creation of this work, the author will play the body to be used purely as a game viewing, structured to be an independent body and the artistic significance of the body. Form in the creation of this work is the general body structure of the entity, which is then explored a visual form of artistic photography and have an abstract impression Susan Sontag in the book of Acts Eyes is written by Seno Gumira Ajidarma;